Response of SO2 and particulate air pollution to local and regional emission controls: A case study in Maryland. Issue 4 (12th April 2016) - He, Hao; Vinnikov, Konstantin Y.; Li, Can; Krotkov, Nickolay A.; Jongeward, Andrew R.; Li, Zhanqing; Stehr, Jeffrey W.; Hains, Jennifer C.; Dickerson, Russell R.
Abstract: This paper addresses the questions of what effect local regulations can have on pollutants with different lifetimes and how surface observations and remotely sensed data can be used to determine the impacts. We investigated the decadal trends of tropospheric sulfur dioxide (SO2 ) and aerosol pollution over Maryland and its surrounding states, using surface, aircraft, and satellite measurements. Aircraft measurements indicated fewer isolated SO2 plumes observed in summers, a ∼40% decrease of column SO2, and a ∼20% decrease of atmospheric optical depth (AOD) over Maryland after the implementation of local regulations on sulfur emissions from power plants (∼90% reduction from 2010). Surface observations of SO2 and particulate matter (PM) concentrations in Maryland show similar trends. OMI SO2 and MODIS AOD observations were used to investigate the column contents of air pollutants over the eastern U.S.; these indicate decreasing trends in column SO2 (∼60% decrease) and AOD (∼20% decrease). The decrease of upwind SO2 emissions also reduced aerosol loadings over the downwind Atlantic Ocean near the coast by ∼20%, while indiscernible changes of the SO2 column were observed. A step change of SO2 emissions in Maryland starting in 2009–2010 had an immediate and profound benefit in terms of local surface SO2 concentrations but a modest impact on aerosol pollution, indicating that short‐lived pollutants are effectively controlled locally, while long‐lived pollutants require regional measures. Key Points: Identify the long‐term trend of sulfur pollution in the eastern U.S. Response of SO2 and sulfate pollution to local and regional control measures Remotely sensed satellite products capture the impacts of recent air pollution control